Religious Thinking of Ashʿarite School - Syafruddin Syafruddin (International Journal of Nusantara Islam, 2019)
The schools of kalam basically arose due to the murder of Caliph Usman bin Affan which ended in the rejection of Mu'awiyah over the caliph Ali bin Abi Talib. The tension between the two continued into the war known as the Siffin war, and that was the beginning of the emergence of the science of kalam. The first stream was the Khawarij sect and was followed by Syi'ah who emerged as a faithful defender of the Caliph Ali bin Abi Talib and Murji'ah who came up with a reaction to the thoughts of the Khawarij. Focusing on the discussion, reason and revelation are always discussed endlessly even though these two streams are like water and oil which cannot be united with the intention that there is always conflict between the two in the aspects of thought and legal products produced by both. In the opinion of the Ashʿarite School of reason and revelation can not be separated but have their own work but the revelation is more important than the mind. The intellect can not define one obligation that can determine one obligation is a revelation. God has many properties such as ‘ilmu, basar, qudrat, hayat and other properties. And what must be known to those who are back and minded Muslims are twenty compulsory properties, twenty traits that are impossible and one must. In short, God has the character. Faith is instituted in the heart, pledged verbally, and accompanied by charity. While disbelievers are doubters in the presence of Allah, doubt on the Messenger, doubts about the Judgment, heaven and others. All the mere deeds of God do not create anything except God, but God has no law made all the way. The act of disbelief is indignant, though how the infidels want good deeds but he is still doing bad deeds. The act of Islam is good, but it is difficult, however, that a believer wants a divorce is not difficult, so a believer can not create it, in short all acts created by Allah Praise be unto Thee the Almighty.